2020
DOI: 10.1111/psyg.12631
|View full text |Cite
|
Sign up to set email alerts
|

Associations between malnutrition and cognitive impairment in an elderly Chinese population: an analysis based on a 7‐year database

Abstract: Aim This study aimed to elucidate whether malnutrition is associated with cognitive impairment in an older Chinese population. Methods A cross‐sectional study was conducted in 2365 participants aged 60 years or older from January 2013 to September 2019. Nutritional status was measured by using the Mini Nutritional Assessment Short Form (MNA‐SF). Cognitive function was assessed with the Mini‐Mental State Examination (MMSE). The relationship between malnutrition or each Mini Nutritional Assessment Short Form dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 38 publications
3
15
1
Order By: Relevance
“…Due to the proposed relationship between long-term dietary patterns and cognitive function, malnutrition has also been linked to cognitive impairment [ 49 , 50 ], although the relationship is complex and difficult to disentangle and more studies are needed on this subject [ 50 ]. Similarly, there is a close interaction between malnutrition and depression [ 51 , 52 , 53 ], but causality is difficult to establish, as the relation is most likely mutual.…”
Section: Impact Of Malnutrition In the Oldmentioning
confidence: 99%
“…Due to the proposed relationship between long-term dietary patterns and cognitive function, malnutrition has also been linked to cognitive impairment [ 49 , 50 ], although the relationship is complex and difficult to disentangle and more studies are needed on this subject [ 50 ]. Similarly, there is a close interaction between malnutrition and depression [ 51 , 52 , 53 ], but causality is difficult to establish, as the relation is most likely mutual.…”
Section: Impact Of Malnutrition In the Oldmentioning
confidence: 99%
“…In particular, it is possible for SCC to have affected the reporting of some variables due to memory problems (e.g., diagnosis of disorders, sleep problems). Second, although a total of 10 chronic conditions were included in the analysis, there may be other conditions such as malnutrition [48], stroke [49], and HIV infection [50], which were not included in the analysis but may be important conditions in relation to cognition. Third, it is also possible that there was misclassification for chronic conditions based on self-reported diagnosis especially in resource-limited settings as under-diagnosis may be common.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Previous studies have demonstrated that nutritional status played a significant role in the progression of cognitive impairment in older patients with dementia or Alzheimer’s disease (AD) ( Ousset et al, 2008 ; Santos et al, 2018 ; Kimura et al, 2019 ; Doorduijn et al, 2020 ). Recent researches have also illustrated that malnutrition was associated with an increased risk of cognitive decline among older adults ( Hsu et al, 2019 ; Assis et al, 2020 ; Mantzorou et al, 2020 ; Yu et al, 2021 ). However, most of the studies have explored the relationship by utilizing Mini Nutritional Assessment (MNA) ( Assis et al, 2020 ; Mantzorou et al, 2020 ) or Mini Nutritional Assessment Short-Form (MNA-SF) ( Hsu et al, 2019 ; Yu et al, 2021 ), but not the Geriatric Nutritional Risk Index (GNRI).…”
Section: Introductionmentioning
confidence: 99%
“…Recent researches have also illustrated that malnutrition was associated with an increased risk of cognitive decline among older adults ( Hsu et al, 2019 ; Assis et al, 2020 ; Mantzorou et al, 2020 ; Yu et al, 2021 ). However, most of the studies have explored the relationship by utilizing Mini Nutritional Assessment (MNA) ( Assis et al, 2020 ; Mantzorou et al, 2020 ) or Mini Nutritional Assessment Short-Form (MNA-SF) ( Hsu et al, 2019 ; Yu et al, 2021 ), but not the Geriatric Nutritional Risk Index (GNRI). MNA and MNA-SF were defined as those not using biological indicators, such as albumin.…”
Section: Introductionmentioning
confidence: 99%